POLA KALIMAT GRAMATIKAL HODO DALAM BAHASA JEPANG - Nani Sunarni (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
This research focuses on studying grammatical sentence patterns hodo in Japanese. The data used is in the form of sentences containing the particle hodo with a noun structure 「(N) + hodo nai/inai」, 「hodo no Nomina」, 「hodo + Predicate/Adjective 」, and 「Numeralia + hodo」. Noun structure sentence patterns 「(N) + hodo nai/inai」means stating the highest degree compared to others. Structured sentence patterns 「hodo no Nomina」meaningful shows the limits and degrees of something expressed by nouns, structured sentence patterns 「hodo + Predicate/Adjective」means stating that something marked by a noun has a very high degree or the most or the most . Next, structured sentence patterns「Numeralia + hodo」means to express the length of time, amount or length of days.